Puisi Du'a karya Khalil Gibran, Mikhail Naimah, Nasib 'Aridah, dan Abdul Masih Haddad (Analisis Semiotika Riffaterre) - Selma Meila Puspita; Yayan Nurbayan; Sofyan Sauri (Jurnal Internasional Pendidikan Bahasa Arab, 2020)
Du'a Poetry is one of the Poems written by Diaspora poets. One work that was born of four modern-century poets, Gibran Khalil Gibran, Mikhail Naimah, Fate of Aridhah and Abdul Masih Hadad. Du'a's poetry is the material object in this paper. Characteristics of Du'a Poetry which is a modern poetry of Mahjar (migrant) not only presents the beauty of its poetic structure and language, it also represents other characters of Mahjar's poetry such as the selection of romantic diction and the acculturation of two Eastern and Western cultures. Mahjar's poetry is also known for its uniqueness in loading philosophical and spiritualist thoughts. Its formal object is Riffaterre's Semiotics. This poem will be analyzed through reading heuristics or mimesis based on the meaning of the dictionary and hermeneutical or retroactive reading. Riffaterre's semiotics believes that in the form of textual poetry, there is a non-textual empty space which is the core of the poem called the hypogram. In the hypogram will be found the central meaning of poetry or matrix. The matrix of this poem is the nature of man in a philosophical perspective. Hypogramatically, this poem is based on the philosophical thought texts of spiritualism about humans. This is seen in the model of poetry, the first actualization of the matrix, in the form of one sentence أنا ما لي وللورى فارفعيني (What am I to myself and others, then lift me). In the end, Ana in poetry Dua transitioned to find a destination where she lived, then anchored on the throne of heaven, the throne of God.